Mathematical Model of Development of an Innovative Education System - Krupa, Tatiana V. (The journal of contemporary issues in business and government, 2021)
Due to in connection with the development of science in all countries there is a demand for young scientists who will be able to conduct successful research and discoveries. The educational system has the goal of organizing educational processes in such a way that students can show better academic performance, and teachers can identify the gap in the student's education and fill it. This research provides a method for developing a mathematical model of the trajectory of the student learning the proposed model was developed taking into account external variables that reflected the students’ characteristics in turninfluencing the learning process and the education. Such student mathematical model for the individual training will decrease the cost for this type of training and at the same time will give all the benefits of the individualized training., In addition, the use of the neural networks to research and predict the properties of the educational trajectory will make it possible to discover the new and effective research methods in the field of learning theory.